Enzymatic hydrolysis of inulin by an immobilized extremophilic inulinase from the halophile bacterium Alkalibacillus filiformis. (1st September 2019) - Yousefi-Mokri, Mahsa; Sharafi, Ali; Rezaei, Shahla; Sadeghian-Abadi, Salar; Imanparast, Somaye; Mogharabi-Manzari, Mehdi; Amanzadeh, Yaghoub; Faramarzi, Mohammad Ali
Abstract: Bacterial inulinases are the key enzymes in the enzymatic hydrolysis of inulin and production of fructooligosaccharides (FOSs) and high fructose syrup (HFS). An extremophilic inulinase was purified from Alkalibacillus filiformis using 80% ethanol precipitation, ultrafiltration, and Q-Sepharose anion exchange chromatography. The purified inulinase was highly active in a wide range of pH, temperature, chemical reagents, and NaCl concentrations. The enzyme immobilization on cobalt ferrite magnetic nanoparticles (CoFe2 O4 MNPs) was carried out by carrier binding method with covalent linkage and showed improved stability and reusability within a broad temperature and pH range, compared with the free enzyme. Using free and immobilized inulinases from A. filiformis, 122 g L −1 and 160 g L −1 fructose with 61% and 80% conversion, respectively, were obtained, with inulin as the substrate. The enzymatic properties, such as notable stability under extreme conditions, make the inulinase from A. filiformis a promising candidate for related biotechnological applications. Graphical abstract: Image 1 Highlights: An extremophile inulinase was isolated from the bacterium Alkalibacillus filiformis. The enzyme was stable against some salt, solvents, chemicals, and pH-temperature ranges. The inulinase immobilization was conducted by covalent attachment on CoFe2 O4 MNPs. The immobilized inulinase was used for production of high fructose syrup. 122 g L −1 and 160 g L −1 fructose were obtained by the free and immobilized enzyme during 48 h.